Clinical case of a patient with focal cortical dysplasia IIa adjacent to the speech center: diagnostic and therapeutic algorithms - N. V. Muzhikina; N. Yu. Koroleva; V. R. Kasumov; P. V. Pushnoy; A. D. Korotkov; I. A. Kotomin; M. V. Kireev (Эпилепсия и пароксизмальные состояния)
A clinical case of a patient with pharmacoresistant epilepsy due to focal cortical dysplasia (PCD) directly adjacent to the speech zone in the left temporal region is presented. The diagnostic search and transition from MRI-negative form to structural focal epilepsy progressed for more than 6 years. It was accounted for by the fact that type IIa vs. IIb FCD is visualized much worse, magnetic resonance imaging (MRI) signs of type IIa FCD are not so prominent, so that this type of dysplasia is often omitted. Functional research methods in epileptology, such as video-electroencephalography monitoring, brain positron emission tomography with 18F-fluorodeoxyglucose, functional MRI of speech zones, allow to more accurately verify the form of epilepsy and determine a scope of surgical treatment. Surgical intervention in carefully selected patients may contribute to favorable outcome of epilepsy (Engel 1, 51-months follow-up), which will lead to improved quality of life.